Mengatasi Perilaku Agresif Pelaku Bullying Melalui Pendekatan Konseling Gestalt Teknik Kursi Kosong - Dyastuti, Susanti (Universitas Negeri Semarang, 2012)
The purpose of this research is to known effort and succesful in contend agresive behaviour of bully by counseling gestalt of empty chair technic. The kinds of this research is action research that have two cycle. Suject of this researchment is two bullies student dan doing agresive behaviour. Method that used in collecting data are interview and observation. Analysis of this researchment data are used analytic and qualitative data. Result of this researchment show changing of agresive behaviour on the bullies student and show decrease of clien agresivity. The conclution of this researchment is agresive behavior of bullies student can prevent used counceling gestalt empty chair technic.